Hamstring-to-Quadriceps Ratio in Female Athletes with a Previous Hamstring Injury, Anterior Cruciate Ligament Reconstruction, and Controls - Eleftherios Kellis; Nikiforos Galanis; Nikolaos Kofotolis (MDPI AG, 2019)
Muscle strength imbalances around the knee are often observed in athletes after anterior cruciate ligament (ACL) surgery and hamstring muscle injury. This study examined three hamstrings-to-quadriceps (H:Q) strength ratio types (conventional, functional, and mixed) in thirteen female athletes with a history of hamstring injury, fourteen basketball players following ACL reconstruction and 34 controls. The conventional (concentric H:Q) peak torque ratio was evaluated at 120°·s−1 and 240°·s−1. The functional (eccentric hamstring to concentric quadriceps) torque ratio was evaluated at 120°·s−1. Finally, the mixed (eccentric hamstrings at 30°·s−1 to concentric quadriceps at 240°·s−1) torque ratio was calculated. Both ACL and the hamstring-injured groups showed a lower quadriceps and hamstrings strength compared with controls (p < 0.05). However, non-significant group differences in the H:Q ratio were found (p > 0.05). Isokinetic assessment of muscle strength may be useful for setting appropriate targets of training programs for athletes with a history of ACL surgery or hamstring strain. However, isokinetic evaluation of the H:Q ratio is not injury—specific and it does not vary between different methods of calculating the H:Q ratio.